HOSPITAL SCHOOLS AS A BRIDGE BETWEEN MEDICAL INSTITUTIONS AND GENERAL EDUCATION SCHOOLS - Qurbonova Maxtuma Fazliddinovna (Bright Mind Publishing, 2025)
Hospital schools represent a specialized educational model designed to ensure the continuity of learning for children and adolescents undergoing long-term or repeated medical treatment. This study examines hospital schools as an integrative bridge between medical institutions and general education schools, emphasizing their pedagogical, social, and developmental significance. The research is grounded in the understanding that education is not only an academic process but also a critical factor in supporting psychological well-being, social inclusion, and personal development during periods of illness. The abstract outlines the conceptual foundations of hospital schooling, highlighting its dual orientation toward educational standards and medical–therapeutic requirements. Particular attention is paid to the role of interdisciplinary collaboration between teachers, healthcare professionals, psychologists, and families in creating a supportive and adaptive learning environment. The study explores how individualized curricula, flexible instructional methods, and inclusive pedagogical approaches enable hospitalized learners to maintain academic progress while accommodating health-related limitations. Furthermore, the abstract emphasizes the relevance of hospital schools within contemporary pedagogical discourse, especially in the context of inclusive education, equity of access, and child-centered learning. By analyzing international practices and contextualizing them within national educational frameworks, the study underscores the potential of hospital schools to function as a sustainable institutional bridge that aligns educational continuity with medical care. The findings presented in this research contribute to the theoretical and practical understanding of hospital pedagogy and offer insights for pedagogical universities, policymakers, and practitioners seeking to strengthen inclusive and flexible education systems.
Keywords: Hospital schools, inclusive education, educational continuity, hospital pedagogy, interdisciplinary collaboration, individualized learning, child-centered education, special educational needs.